Relationship of Authoritarian Parenting on the development of Pre-School Age Children in Karya Indah Vilage Working Area UPT Puskesmas Pantai Cermin - Nelly Karlinah; Berliana Irianti (Institute of Computer Science (IOCS), 2021)
Health efforts carried out since the child is still in the womb until the first five years of life, aimed at maintaining its survival are aspects that explain the formation of development, both physically and psychosocially. rude and language. Child development is strongly influenced by the environment and the interaction between children and their parents. The purpose of the study was to determine the relationship between authoritarian parenting and the development of pre-school children. This type of research is descriptive analytic with a cross sectional design. The time of the research was carried out in June-November 2021. The place of research was carried out in the village of Karya Indah. The sample in this study were 88 respondents with random sampling technique. The research instrument used a questionnaire. Data analysis was carried out univariate and bivariate. The univariate result of the majority of parenting patterns being non-authoritarian is 75.0%. Bivariate results using the Chi-Square test showed that there is a relationship between authoritarian parenting and the development of pre-school children in Karya Indah village with a P value of 0.002 <0.05